2005
DOI: 10.1128/jvi.79.16.10147-10154.2005
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-Activated Protein Kinase-Dependent Hyperinduction of Tumor Necrosis Factor Alpha Expression in Response to Avian Influenza Virus H5N1

Abstract: Avian influenza A virus subtype H5N1 can infect humans to cause a severe viral pneumonia with mortality rates of more than 30%. The biological basis for this unusual disease severity is not fully understood. We previously demonstrated that in contrast to human influenza A virus subtypes including H1N1 or H3N2, the H5N1 virus associated with the "bird flu" outbreak in Hong Kong in 1997 (H5N1/97) hyperinduces proinflammatory cytokines, including tumor necrosis factor alpha (TNF-␣), in primary human macrophages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 36 publications
8
140
0
Order By: Relevance
“…Previous reports have shown that p38 kinase regulates influenza virus-induced RANTES expression in bronchial epithelial cells (39) and is involved in TNF-␣ production during H5N1 infection (18). Therefore, we explored the effect of IRF3 knockdown and p38 kinase inhibitor treatment both singly and in combination on H5N1-induced cytokine and chemokine expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that p38 kinase regulates influenza virus-induced RANTES expression in bronchial epithelial cells (39) and is involved in TNF-␣ production during H5N1 infection (18). Therefore, we explored the effect of IRF3 knockdown and p38 kinase inhibitor treatment both singly and in combination on H5N1-induced cytokine and chemokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…p38 kinase is essential for virus-induced cytokine production by bronchial epithelial cells including IL-6, IL-8, and GM-CSF (15)(16)(17). We have shown that p38 kinase is involved in the hyperinduction of TNF-␣ expression in H5N1-infected macrophages (18), although the mechanisms underlying this hyperinduction of cytokine by H5N1 influenza virus have not been elucidated. Recent studies have reported hyperactivation of phospho-p38 kinase with increased cytokine concentrations in plasma samples of patients infected with severe seasonal influenza A virus (19).…”
Section: Induction Of Proinflammatory Cytokines In Primary Humanmentioning
confidence: 93%
“…Recently, Lee et al (6) showed in a macrophage model that p38 MAPK signaling is of major importance for the hypercytokinemia in H5N1 influenza virus-infected individuals (6). The p38 MAPK signaling pathway triggers a broad spectrum of transcription factors, among them activating transcription factor 2.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen micrograms of the empty retroviral pCFG5-IEGZ HA vector or pCFG5-IEGZ IKK2KD expressing dominant negative IKK2 (29) was transfected into 3 ϫ 10 6 Phoenix packaging cells with polyethyleneimine as described previously for HEK293 (33) and selected with 250 g/ml Zeocin (Invitrogen) for 2 wk to gain stable producer cells. Three ϫ 10 6 stable producer cells were seeded on 100-mm dishes 48 h before transduction.…”
Section: Retroviral Gene Transfermentioning
confidence: 99%
See 1 more Smart Citation